Implementing Kurikulum Merdeka: Teachers’ Strategy in Teaching English in Elementary School - Virda Rizki Ananda; Nida Husna; Farida Hamid (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study explores the strategies employed by elementary school English teachers in implementing the Merdeka Curriculum. The research focuses on understanding how teachers adapt their instructional practices, utilize resources, and address challenges in fostering student-centered learning. Data were collected from five teachers in Jakarta using a qualitative descriptive approach, supported by questionnaires. The findings reveal that teachers use diverse teaching resources, active learning methods, and interdisciplinary integration to engage students and improve communication skills. However, challenges such as limited instructional time, inadequate facilities, and uneven training opportunities hinder the full implementation of the curriculum. This study underscores the importance of professional development and resource allocation to enhance curriculum delivery, offering insights into improving English language education at the elementary level.